Springs of action : understanding intentional behavior - Mele, Alfred R., 1951- (Oxford University Press, 1992)
Tackling some central problems in the philosophy of action, Mele constructs an explanatory model for intentional behavior, locating the place and significance of such mental phenomena as beliefs, desires, reason, and intentions in the etiology of intentional action. Part One comprises a comprehensive examination of the standard treatments of the relations between desires, beliefs, and actions. In Part Two, Mele goes on to develop a subtle and well-defended view that the motivational role of intentions is of a different sort from that of beliefs and desires. Mele, also offers a provocative expl.